Mendelian randomization and bioinformatics unveil potential links between gut microbial genera and colorectal cancer - Wu, Long; Wu, Huan; Huang, Fei; Mu, Song; Li, Xiao-Yun; Zhang, Bao-Fang; Zhen, Yun-Huan; Li, Hai-Yang (Frontiers in Genetics, 2024)
BackgroundColorectal cancer (CRC) poses a significant global health burden, with high incidence and mortality rates. Despite advances in diagnostic and therapeutic modalities, early diagnosis remains critical for improved outcomes. Recent research has realized the important role of gut microbiota in CRC development, highlighting the need to elucidate potential relationships.MethodsIn this study, we employed Mendelian randomization (MR) to establish a robust potential link between gut microbial genera and CRC. Data from the MiBioGen database provided curated genome-wide association study (GWAS) summary datasets for microbial genera, while the Finngen database provided CRC outcome data. Instrumental variables (IVs) were identified based on genetic variants associated with gut microbiota. Various MR methods, including Inverse Variance Weighted (IVW), Weighted Median, Weighted Mode, Simple Mode, and MR-Egger, were employed to estimate potential effects. Functional analysis of genes near single nucleotide polymorphisms (SNPs) was performed to unravel potential pathways.ResultsAnalysis of microbial genera identified five potentially associated with CRC: Eubacterium fissicatena group, Anaerofilum, Defluviitaleaceae UCG011, Ruminococcus 2, and Sutterella. Notably, Defluviitaleaceae UCG011 emerged as the only risk factor. Gene analysis revealed hub genes PTPRD and DSCAM near Defluviitaleaceae UCG011 associated SNPs. Expression analysis showed that PTPRD decreased in colon cancer and DSCAM decreased in rectal cancer. The methylation status of the PTPRD gene promoter region indicated potential regulatory alterations.ConclusionThis study establishes a potential relationship between five specific gut microbial genera, particularly Defluviitaleaceae UCG011, and CRC. Hub genes PTPRD and DSCAM provide insights into potential molecular mechanisms, suggesting the potential role of Defluviitaleaceae UCG011 in modulating the initiation and progression of CRC. Further research is essential to validate these associations and delve deeper into therapeutic implications.